Issues of International and Interchurch Relations in the Work of Holy Council 1917–1918 of the Orthodox Russian Church - A. I. Mramornov (Vestnik MGIMO-Universiteta)
The convocation of the Local Council in 1917, the first Council in over two centuries, had a great significance for the internal life of the Orthodox Church of Russia. But in a period when the World War was still ongoing and there were pressing issues to resolve in the sphere of cooperation of Russian Orthodoxy with other orthodox and non-orthodox churches, the Local Council could not but touch upon the international and inter-church issues. For the first time in the history of Russian Church the official ecclesiastical forum was attended by official elected delegates who served abroad and who could bring the opinion of the foreign part of the Russian Church to its «maternal» part and to provide the mutually beneficial exchange of practices and opinions. Moreover, in a situation when the church was liberated from the tutelage of the state, it became possible to engage with foreign religious organizations not through social organizations or the Ministry of Foreign Affairs, but directly. This opened a way for creating the Church’s own structures which would be responsible for contacts with other confessions, including Old-Catholics and Anglicans, with whom there had already been lengthy unofficial dialogue. The efforts of some historians and publicists shaping contemporary discourse in Russia depict the restoration of the Patriarchate in the Russian Church as the only important act of the Council are challenged by the material presented in this article, which shows how the Council constructed the future position of Russian Orthodoxy in dialogue with the non-Orthodox churches, in its presence abroad and its missions in non-Christian countries. The word of the Council in this sphere was completely new and never before told. The Council was ahead of its time in the issues of international connections (like in many other spheres of its work). Many issues at the Council were expressed for the first time or in a completely new way. How to manage the missions abroad (in Japan, China, Korea, Urmia, and Palestine)? The Council, occupied with the internal problems in the situation of the beginning of persecution against it, could not abandon these missions. How was it possible to unite Russian emigrants abroad? The idea of Paris as a centre of their unification was expressed for the first time at the Council. The scholars who touched upon these issues before analyzed them through the concept of ecumenism (following the participation of the Russian Church in the ecumenical movement). But it seems more appropriate to research them in the context of the time of the Council itself, since it was a time that preceded the emergence of the Ecumenical Movement proper. The author of the article draws a conclusion that during the year of the Council (August 1917 – September 1918) the issues of international and inter-church relationships transformed in its agenda from being of secondary to primary importance. This conclusion allows us to challenge the dismissive perspective that the Moscow Council 1917-1918 was ineffective. Although it did not have time to complete its agenda, the Council was ahead of its time and contributed much for the future mission of the Russian Church in the modern world.